Methods of studying the dynamics of some sleep quality indexes in Antarctic winterers - Shylo, O.V.; Lutsenko, D.G.; Danylenko, K.M.; Babiychuk, G.O.; Moiseyenko, Ye.V. (Ukrainian Antarctic Journal, 2017)
Disturbances in sleep quality can be accompanied by circadian rhythm disorders and lead to the development of pathology, including those from the side of psychophysiological and psychological functions. In many participants of Antarctic expeditions the “Antarctic syndrome” is developed. The violation of the normal rhythm of sleep is the key component of the syndrome. Objectives. Therefore, in order to elucidate the diagnostic relevance of subjective sleep changes obtained using questionnaire and a method of recording objective indicators of motor activity in sleep using smart technologies, we performed the sleep study of individual wintering volunteers in the Antarctic station conditions. Methods. Twelve winterers of the 21st Ukrainian Antarctic expedition (from 22 to 63 years old) participated in the studies, the average age was 39.25 years, all men. IDS-SR30 questionnaire was used to determine the personal evaluation of sleep quality. In addition, four people (43, 51, 23, 23 years old, the first winter in Antarctica) participated in the study aimed at identifying objective changes in sleep and elucidating the diagnostic relevance of the method of recording objective indicators of motor activity in sleep using smart technologies during the wintering period with the use of personal smartphones with installed software Sleep as Android (Urbandroid Team) and a specially developed program to read data from the smartphone accelerometer. Results. Analysis of winterers testing during stay at the station using the IDS-SR30 questionnaire showed that the dynamics of subjective sleep quality problems were characterized by individual features, but their peak amounts occurred during the middle of the Antarctic winter, which may be due to almost total absence of a daily photoperiod in the season. It should be mentioned that in individual winterers the sleep problems have remained until the end of the expedition, which can increase the load on the adaptive reserves of the organism and lead to the development of state of fatigue and chronic stress. The marked dynamics of subjective characteristics and the estimated value of the sleep quality in winterers in the Antarctic dictated the necessity of reinforcing the results with objective indicators, like total sleep time and deep sleep duration, which were calculated on the basis of registration of motor activity in sleep recorded using smart technologies. Conclusions. The use of test packages for the psychological diagnosis of in winterers will allow to objectify the individual dynamic changes in the characteristics of daily sleep duration and its quality during the whole expeditionary period of stay in the Antarctica. This makes it possible to expand the possibilities for assessing the psychophysiological state of winterers by analyzing quality indices of the sleep and its duration, which is based on the recording of motor activity in sleep.